The Role of Demographic Variables on Knowledge-Sharing Behaviour among Academicians - Haji Omar, Arenawati Sehat; Ahmad Zaidi Adruce, Shahren (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Every organisation needs to recognize knowledge as an important asset for individuals as well as the organisation itself order to survive in competitive environment. Since knowledge sharing is a critical activity for academicians, it has to be enhanced by stimulating individuals to share their knowledge voluntarily with other individuals and to contribute to the organizational knowledge base. Hence, institutions should focus on motivating the academicians to share knowledge among themselves, across the departments, institutions, and industries; and to contribute to the knowledge base. Objective: To identify the role of demographic variables on knowledgesharing behaviour among academicians. Results: Every individual’s attitude is subject to his own personal traits and to the environment or surrounding that the individual belongs to or is attached with. In the university, knowledge is intensively created and disseminated through research and publication. This is the most probable due to the belief that individual knowledge is not necessarily easy to be retrieved. Thus academicians play their roles as knowledge providers by transferring and sharing their knowledge through written contributions, organisational communications, personal interaction, and communities of practices activities. Motivational factors may be categorized according to different age, gender, designation, and organizational tenure of the academicians. This topic prompts individuals to actually oblige in sharing the knowledge. The reason is due to the fact that knowledge-sharing actually give more benefits than pitfalls. Individuals should require motivation to exchange the knowledge for the organization to gain competitive advantage. Conclusion: This concept paper provides an insight on the role of demographic characteristics towards knowledge-sharing behaviour among the academicians.